Optimization of Human Resources to Improve Corporate Financial Health: A Qualitative Perspective and Best Practices - Hamsyah; Arimbawa, I Gede Arya Pering; Rostini; Bakri, Risna Melati Sukma; Muhammad, A Fadel (Economics and Business Journal (ECBIS), 2024)
In the era of globalization and increasingly intense competition, the management of Human Resources (HR) has become a crucial factor for ensuring company sustainability and growth. This study aims to explore the impact of HR optimization on a company's financial health using a qualitative approach. Employing a case study methodology, the research analyzes companies that have successfully implemented effective HR strategies, including employee development, competitive compensation policies, performance management, and wellness programs. Data was collected through in-depth interviews with HR managers, executives, and employees, as well as internal document analysis and direct workplace observation. The findings indicate that effective HR practices can reduce costs, enhance productivity, and lower turnover rates, all contributing to improved financial performance. The results support Wright and McMahan's (2011) theory that effective HR management acts as an enabler for achieving competitive advantage. The study also aligns with Huselid’s (1995) research, which highlights the importance of competitive compensation policies in boosting productivity and financial health. This research underscores the significance of aligning HR strategies with financial goals and adopting best practices in HR management to improve operational efficiency and achieve sustainable financial objectives.